Macropalaeontology and stratigraphy of lacustrine Miocene deposits at Crnika beach on the Island of Pag (Croatia) - Bulić, Jeronim (Array, 2009)
Summary: The sequence of Miocene fossiliferous marls of the Crnika beach, along the south west shore of Pag Bay, consists of an alternation of silty and clayey marls, sandstones, coaly clays, coal-bearing strata and sparse intercalations of bentonite in the older part, and of an alternation of calcitic marls and organogenic fossiliferous limestones with several coal strata in the younger part. Some of the strata are highly fossiliferous and rich in various species of freshwater gastropods of the genera Melanopsis, Theodoxus, Pyrgula, Prososthenia, Orygoceras and Valvata with the new species V. (?Costovalvata) pagana. Bivalves are represented by the genera Congeria, Unio, Pisidium. There is also, a rich ostracod assemblage, and remains of flora: twigs, leaves and seeds of higher and lower plants, and agglomerations of aquatic grasses and algae. Fish bones and teeth, as well as the crocodile tooth, are not particularly common, but they do help to complement the image of the diversity of the biological association that lived in the ancient lake and along its shores. According to facies analysis, the Miocene deposits of the Island of Pag, were deposited on the south-western edge of Paratethys, which has been moved more westward and south-westward within Croatian territory